Digital Television in Ireland: Local Forces in a Global Context - Corcoran, Farrel (Javnost-The Public, 2002)
It is becoming clear that as digital television is rolled out across Europe, it is now in a "shake-out" phase where some institutional actors fail and others consolidate their activities. Digital Terrestrial Television (DTT), hailed a few years ago as the platform most likely to succeed because of its universal reach and its low cost to both signal distributors and viewers, is now suffering severe reversals in many parts of Europe. This paper explores the reasons for this in one part of Europe, where DTT didn't even get to the point of being launched, despite the fact that intense planning took place over several years, involving both the public service broadcaster RTE and the Government. Political inertia, long delays and the collapse of global investor confidence in new media combined to freeze out the development of DTT and open the way for global operators to launch both cable and satellite platforms and seize new opportunities in a wide-open Irish market. The lesson for other parts of Europe is how easily democratic control of a major new communication technology can slip away, despite the best intentions of planners at the highest level, and how global forces, responding only to market imperatives, slip in to fill the void when national planning collapses. A case study approach demonstrates the detail of how the efficacy of national sovereignty in communication policy is eroded in an environment that is increasingly globalised.